Microsimulation-Based Traffic Management on Urban Roads in Indonesia - Pradana, Ikhlas Maddinah; Azalia, Salsabila; Muda, Teuku Satria; Hariani, Mira Lestira (PT FORMOSA CENDEKIA GLOBAL, 2025)
Congestion in urban areas is not only influenced by the high volume of vehicles, but also by U-Turn maneuver activities that can cause conflicts and reduce traffic performance. This study aims to evaluate the effect of U-Turn facilities on road performance and provide recommendations for handling them. The method used is microscopic simulation using PTV VISSIM software, with reference to evaluation parameters based on the 2023 Indonesian Road Capacity Guidelines (PKJI), namely the degree of saturation (DJ), delay, and Level of Service. The results of the study indicate that in the next 10 years there will be a decline in the performance of the analyzed U-Turn. This study analyzes 3 (three) alternative handling solutions in the form of traffic management on U-Turns and produces the best recommendations in the form of full opening of U-Turns 1 and 4, partial closure of U-Turns 2, and full closure of U-Turns 5 and 6 which can improve traffic performance on U-Turns to be more optimal (reducing delay values and increasing Level of Service values).